Comparative Integrated Omics Analysis of the Hfq Regulon in Bordetella pertussis - Dienstbier, Ana; Amman, Fabian; Štipl, Daniel; Petráčková, Denisa; Večerek, Branislav (International journal of molecular sciences, 2019)
Bordetella pertussis is a Gram-negative strictly human pathogen of the respiratory tract and the etiological agent of whooping cough (pertussis). Previously, we have shown that RNA chaperone Hfq is required for virulence of B. pertussis. Furthermore, microarray analysis revealed that a large number of genes are affected by the lack of Hfq. This study represents the first attempt to characterize the Hfq regulon in bacterial pathogen using an integrative omics approach. Gene expression profiles were analyzed by RNA-seq and protein amounts in cell-associated and cell-free fractions were determined by LC-MS/MS technique. Comparative analysis of transcriptomic and proteomic data revealed solid correlation (r2 = 0.4) considering the role of Hfq in post-transcriptional control of gene expression. Importantly, our study confirms and further enlightens the role of Hfq in pathogenicity of B. pertussis as it shows that Δhfq strain displays strongly impaired secretion of substrates of Type III secretion system (T3SS) and substantially reduced resistance to serum killing. On the other hand, significantly increased production of proteins implicated in transport of important metabolites and essential nutrients observed in the mutant seems to compensate for the physiological defect introduced by the deletion of the hfq gene.
Keywords: Gene Ontology; proteom; Host Factor 1 Protein; Chromatography, Liquid; Humans; Tandem Mass Spectrometry; genová ontologie; Proteomics; serum resistance; sekreční systém typu III; Hfq; lidé; Bordetella pertussis; regulon; proteomika; výpočetní biologie; regulace genové exprese u bakterií; tandemová hmotnostní spektrometrie; omics analysis; Computational Biology; chromatografie kapalinová; Type III Secretion Systems; stanovení celkové genové exprese; Regulon; transkriptom; protein hostitelského faktoru 1; vysoce účinné nukleotidové sekvenování; Gene Expression Regulation, Bacterial; Transcriptome; High-Throughput Nucleotide Sequencing; Proteome; Gene Expression Profiling; solute-binding proteins; T3SS